Analysis of the Use of The Simponi Application on Improving the Performance of State Civil Apparatus - Vuryanto, Vuryanto; Muthalib, Abdul Azis; Yuana, Indira (International Journal of Management and Education in Human Development, 2024)
This study aims to determine and analyze 1) the performance of ASN of the Department of Public Works, Construction Development and Spatial Planning of Southeast Sulawesi Province with the use of the Simponi application, 2) Obstacles faced in order to encourage increased ASN performance the application of the Simponi Application. and 3) Efforts that have been made to overcome obstacles faced in order to improve the ASN performance with the application of the Simponi Application. This type of research is a qualitative descriptive study intended to obtain an overview and information related to the description of ASN performance with the use of the Simponi ASN application within the Department of Public Works, Construction Development and Spatial Planning of Southeast Sulawesi Province. This research was conducted at the Office of the Department of Public Works, ConstructionDevelopment and Spatial Planning of Southeast Sulawesi Province from August - September 2024. The results of the study indicate that 1) the performance of ASN of the Department of Public Works, Construction Development and Spatial Planning of Southeast Sulawesi Province with the use of the Simponi application can be seen from the aspectsof quantity, quality, time, cost, service orientation, integrity, commitment, discipline, cooperation and leadership. 2) the obstacles faced in order to encourage the improvement of the ASN performance with the implementation of the Simponi Application are from the aspects of quantity, quality, time, service orientation, integrity, commitment, discipline and leadership and 3) efforts that have been made in overcoming the obstacles faced in order to improve the ASN performance with the implementation of the Simponi Application including the role of leaders, good communication, harmonious working atmosphere, provision of supporting work facilities, work motivation fromemployees, periodic evaluations.